Images in World 2.0 - Instructions for use (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2019)
In the essays’ collection The Uses of Images. Studies in the Social Function of Art and Visual Communication (1999), Ernst Gombrich states that images demand in Western society is so significant that it is possible to consider a family without a television, like lacking something. Addressing his thoughts to fundamental requirements on the basis of visual media  – first of all, clarity and communication –  the art historian reminds us the educational role carried out by images in Western culture till latest past, for example in the case of handbooks or encyclopedias. Meantime Gombrich points out how “visual aids” provide a kind of “pictorial instructions”, emphasizing how only few people think that understanding images, both the drawn ones and the in motions ones, is easier when we add verbal descriptions. In light of such considerations, it could be useful to analyze what occurs in web communication, made up with the mutual relationship of images and short texts. The question arising from this paper aims in fact be: what and how does the role of images change in the internet age? Together with the purposes of knowledge and communication, it powerfully opens a new dimension made of images to share: digitization in communication provides new collective knowledge and experience. Furthermore, as some communication’s sociologists affirm, if change in the media seems to drive our society toward a growing confusion between real and unconscious, generating actual showcases to amplify social life (Codeluppi 2012), nowadays is rather in Internet that such process seems to be effective. In virtual places some interpersonal relationships arise and become durable, meantime debates occur to lead ideas and enrich knowledge just possessed by society groups: digital technology, supported by “visual aids”, so allows a new social perception and a growing visibility in the new world 2.0.